Development of starch biobased and biodegradable plastics for their use in trays for food-packaging - Lopez-Gil, A.; Rodriguez-Perez, M. A.; De Saja, J. A.; Bellucci, F. S. [UNESP]; Ardanuy, M. (My University, 2011)
This research work develops new methods to produce biodegradable starch-based trays for the purpose of replacing expanded polystyrene in the food packaging market. The starch based biopolymers present several drawbacks like poor mechanical properties and very high density. In order to overcome these drawbacks two research lines have been set up: blending thermoplastic starch with biobased reinforcements from agricultural wastes like barley straw and grape wastes, and testing the foamability of these materials with a Microwave-foaming method.
Keywords: Barley straw; Biobased polymer; Biodegradable polymers; Microwave; Starch foams; Bio-based polymers; Biobased; Biodegradable plastics; Expanded polystyrene; Foamability; Food packaging markets; Grape waste; High density; Starch-based; Thermoplastic starch; Biopolymers; Blending; Materials testing; Mechanical properties; Microwaves; Plastic products; Polystyrenes; Starch; Straw